Transcriptome sequencing combined with experimental verification to explore potential key genes related to uric acid in diabetic retinopathy - Haiming Liang; Tianqi Yang; Feina Lu; Lixia Lin; Hao Liang (PLoS ONE, 2026)
Purpose Diabetic retinopathy (DR), a major microvascular complication of diabetes and leading global blindness cause, involves uric acid (UA) in its onset and progression. This study aimed to identify UA-related genes (UARGs) in DR and clarify their molecular mechanisms for improved diagnosis and treatment. Methods Using public database transcriptome data, key UARGs were screened via differential expression analysis, machine learning, receiver operating characteristic (ROC) analysis, and expression profiling, followed by gene set enrichment analysis (GSEA), immune infiltration analysis, molecular regulatory network construction, and clinical validation with reverse transcription quantitative polymerase chain reaction (RT-qPCR). Results MMP15 and FOXK1 were identified as potential key genes, with significantly elevated expression in DR patient blood samples. GSEA showed MMP15 enriched in Apc targets requiring Myc and Smarca2 targets up, and FOXK1 in phosphatidylinositol signaling system and proteasome. Immune infiltration analysis revealed differences in 7 immune cell types, with central memory CD8 T cells and natural killer cells showing the strongest positive correlation; MMP15 was negatively correlated with NK cells, and FOXK1 with central memory CD4 T cells and effector memory CD8 T cells. Twelve transcription factors (e.g., HOXB7, CATA6) jointly targeted both genes. Conclusion MMP15 and FOXK1 were identified as potential key genes associated with uric acid in DR, which may provide a reference for further exploration of the pathogenesis and targeted therapy of DR.